Differentiated Learning Technology on Science Education to Students Learning Outcomes - Rini Hidayati; Fitri Eriyanti (Postgraduate, University of Mataram, 2023)
Enhancing student learning by matching student characteristics with learning and assessment, using not just one strategy but a combination of strategies. This research is an experimental research on the use of Differentiated Learning model. Differentiated learning model is a learning model that accommodates the differences that exist in students, be it abilities, learning styles, interests, talents etc.. This study aims to see the effect of using a differentiated learning model on the learning outcomes of class X students in the sociology subject matter of social research at SMAN 2 West Sumatra. This research is a Quasi experimental research that uses The Nonequivalent Control Group design by using experimental class and control class. The data processed in this study are data from the pretest and post-test results from the experimental class and control class in accordance with The Nonequivalent Control Group design.After conducting several data tests in this study, it is proven that differentiated learning models can improve learning outcomes, and this can prove the research hypothesis that there is a significant influence between differentiated learning models and learning outcomes